Overexpression of ameloblastin in secretory ameloblasts results in demarcated, hypomineralized opacities in enamel - Chun, Yong-Hee Patricia; Tan, Chunyan; Villanueva, Omar; Colley, Madeline E.; Quintanilla, Travis J.; Basiouny, Mohamed S.; Hartel, Caldonia A.; Critchfield, Cameron S.; Bach, Stephan B. H.; Fajardo, Roberto J.; Pham, Cong-Dat (Frontiers in Physiology, 2024)
Developmental defects of enamel manifest before tooth eruption and include amelogenesis imperfecta, a rare disease of underlying gene mutations and Molar-incisor hypomineralization (MIH), a prevalent disease in children originating from environmental and epigenetic factors.MIH enamel presents as abnormal enamel marked by loss of translucency, demarcation between healthy and affected enamel, and reduced mineral content. The pathophysiology of opaque, demarcated enamel lesions is not understood, however, the retention of enamel proteins in the matrix has been suggested. Ameloblastin (Ambn) is an enamel protein of the secreted calcium-binding phosphoproteins (SCPP) that is critical for enamel formation. When the Ambn gene is mutated or deleted, teeth are affected by hypoplastic amelogenesis imperfecta. In this study, enamel formation in mice was analyzed when transgenic Ambn was overexpressed from the amelogenin promoter encoding full-length Ambn. Ambn was under-and overexpressed at six increasing concentrations in separate mouse lines. Mice overexpressing Ambn displayed opaque enamel at low concentration and demarcated lesions at high concentrations. The severity of enamel lesions increased starting from the inner enamel close to the dentino-enamel junction (DEJ) to span the entire width of the enamel layer in demarcated areas. Associated with opaque enamel were 17-kDa Ambn cleavage products, a prolonged secretory stage, and a thin basement membrane in maturation stage. Ambn accumulations found in the innermost enamel close to the DEJ and the mineralization front, correlated to reduced mineral content. Demarcated enamel lesions were associated with Ambn species of 17 kDa and higher, prolonged secretory and transition stages, thin basement membrane and shortened maturation stages. Hypomineralized opacities were delineated against surrounding mineralized enamel and adjacent to ameloblasts detached from the enamel surface. Inefficient Ambn cleavage, loss of contact between ameloblasts and altered basement membrane curtailed the endocytic activity, thus enamel proteins remained unresorbed in the matrix.Ameloblasts have the ability to distinguish between Ambn concentration and Ambn cleavage products through finely tuned feedback mechanisms. The under -or overexpression of Ambn in murine secretory ameloblasts results in either hypoplastic amelogenesis imperfecta or hypomineralization with opaque or sharply demarcated boundaries of lesions, similar to MIH.